RANCANG BANGUN GPS UNTUK MENGIDENTIFIKASI BAHAYA NAVIGASI TERDEKAT PADA KAPAL NELAYAN TRADISIONAL - Noviarianto Noviarianto; P Tony Kusumartono; Amthori Anwar; Turahyo Turahyo (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2022)
The Global Positioning System (GPS) is a navigation aid tool to assist in positioning. The use of gps is necessary because in the middle of the sea positioning is quite tricky to do. On traditional fishing boats the use of this equipment is still small. Consideration of the price which is relatively expensive and the knowledge of fishermen in its use is still minimal. This study aims to create a gps device using the ublox Neo-6M sensor. The microcontroller performs the calculation process and displays the parameters on the 20x4 character LCD screen. LCD displays real time DMS position, distance meter, direction to the reference point, knot speed, and date. Reference points as markers of navigational hazards such as buildings and installations in the water, ship hulls, reefs, sandbars and mines. In this study, 4 reference points with different distances and directions were determined in the area around the campus. When the GPS is in a position more than 300m, the CP and BRG markings on the screen do not show certain numbers. If the gps moves closer to one of the points at a distance of less than 300m then the CP screen shows the distance meter number. BRG shows the direction from the gps point to the nearest point. The test results in the field show that the tool can provide information in accordance with the program that has been made. The accuracy obtained from points is about 5m depending on the weather and environmental disturbances such as trees.